The Resource Cost of Irredeemable Paper Money - Friedman, Milton (Journal of Political Economy, 1986)
Since 1971, no major currency has a formal link to a commodity. For the first time in history, every currency is wholly irredeemable, not as a temporary expedient but as a permanent matter. Monetary economists have generally treated irredeemable paper money as involving negligible real resource costs compared with a commodity currency. To judge from recent experience, that view is clearly false as a result of the decline in long-term price predictability. A key question for the future is, What if any substitute for a commodity standard will emerge as a long-term anchor for the price level?